High-throughput characterisation of bull semen motility using differential dynamic microscopy. - Alys Jepson; Jochen Arlt; Jonathan Statham; Mark Spilman; Katie Burton; Tiffany Wood; Wilson C K Poon; Vincent A Martinez (PLoS ONE)
We report a high-throughput technique for characterising the motility of spermatozoa using differential dynamic microscopy. A movie with large field of view (∼10mm2) records thousands of cells (e.g. ≈ 5000 cells even at a low cell density of 20 × 106 cells/ml) at once and yields averaged measurements of the mean ([Formula: see text]) and standard deviation (σ) of the swimming speed, head oscillation amplitude (A0) and frequency (f0), and the fraction of motile spermatozoa (α). Interestingly, we found that the measurement of α is facilitated because the swimming spermatozoa enhance the motion of the non-swimming population. We demonstrate the ease and rapidity of our method by performing on-farm characterisation of bull spermatozoa motility, and validate the technique by comparing laboratory measurements with tracking. Our results confirm the long-standing theoretical prediction that [Formula: see text] for swimming spermatozoa.